Protecting the funds of mobile money customers in civil law jurisdictions - David Ramos; Javier Solana; Ross P. Buckley; Jonathan Greenacre (University of Oxford, Global Economic Governance Programme (GEG), 2015)
The provision of financial services through mobile phones is a powerful tool to foster financial inclusion in developing countries. Yet, it raises important regulatory questions. Given the vulnerability of the vast majority of potential customers of these services, one of the most pressing issues is the protection of customers' funds. In common law countries, trust law is an effective response to these concerns. In civil law jurisdictions however, in the absence of trusts and any directly comparable legal instrument, protection of customers' funds is more difficult. This paper identifies the theoretical and practical problems that regulators in civil law jurisdictions might face when trying to protect customers' funds and explores how fiduciary contracts, mandate contracts and direct regulation might help to achieve that goal. It also offers a series of practical recommendations for policymakers in developing countries that lay out different regulatory options that combine private law and regulation.
Keywords: 330; Finanzielle Inklusion; Informeller Finanzsektor; Elektronisches Geld; Finanzmarktregulierung; Rechtsdurchsetzung; Entwicklungsländer